Spatial Distribution Patterns and Morphological Characteristics of Microplastics in Brackish Waters of Kendari Bay Estuary, Indonesia - Wa Ode Nanang Trisna Dewi; Desy Fadilah Adina Putri (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to characterize microplastics based on variations in their physical form and size and to assess their abundance in the brackish waters of Kendari Bay. Purposive sampling was conducted at three stations representing port and shipping activities, residential areas, and mangrove habitats. Three biological replicates and three technical replicates were collected, yielding 18 samples comprising nine surface-water samples and nine sediment samples. The data were analyzed using descriptive frequency analysis, and the coordinates of all sampling locations were recorded using a Global Positioning System (GPS). The highest microplastic abundance was observed in the port and shipping zone, with 11,460 particles per 150 mL of water and 83 particles g⁻¹ of sediment, indicating that this zone was the primary accumulation area. This was followed by the mangrove area, with 10,620 particles per 150 mL of water and 77 particles g⁻¹ of sediment, and the residential area, with 10,200 particles per 150 mL of water and 68.4 particles g⁻¹ of sediment. Four microplastic forms were identified: fibers, films, fragments, and foams. Foam was the dominant form in both environmental matrices, indicating a substantial contribution from expanded polystyrene (EPS) waste. Most particles were smaller than 0.27 mm, suggesting advanced fragmentation processes in the environment. Based on their color characteristics, the microplastics were predominantly black (37%) and transparent (31%), indicating extensive environmental weathering, followed by yellow (13%), green (13%), and blue (6%). These findings provide an evidence-based foundation for developing policies to control EPS packaging waste across upstream and coastal areas. They also highlight the urgent need to restore mangrove forests as natural filters to reduce the accumulation of microplastics in Kendari Bay.